Uwaga, ekran, akcja, reakcja. Czym jest dokument interaktywny – perspektywy rozwoju w Polsce na podstawie badań - Desponds, Anna; Szylar, Anna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2018)
Interactive documentaries bring new possibilities of artistic expression. They allow innovative ways of engaging the viewer, personalizing experiences, and building a community. At the same time interactive documentaries bring challenges: the need of new production skills, openness to experimentation, the development of new financing models. There is still a need to create a language to describe new formats. The semantic elusiveity of this area seems to be reflected in its market position. The genre is suspended between film, documentary film and computer games and both the audience and the distributors have difficulties defining it. This text is an attempt to describe what an interactive documentary might be, what sets it apart from other formats, and what’s the viewer’s role in this type of audio-visual formats. We present a few flagship projects from different countries and we look at the Polish audio-visual industry. We conducted a survey, asking Polish artists working on so-called new narratives about their work conditions and the biggest challenges they are facing. The second part of the text covers the results of our study.